Evaluation of a needle disinfectant technique to reduce infection‐related hospitalisation after transrectal prostate biopsy. (3rd September 2017) - Auffenberg, Gregory B.; Qi, Ji; Gao, Yuqing; Miller, David C.; Ye, Zaojun; Brachulis, Andrew; Linsell, Susan; Gandhi, Tejal N.; Kraklau, David; Montie, James E.; Ghani, Khurshid R.
Abstract : Objectives: To determine whether a needle disinfectant step during transrectal ultrasonography (TRUS)‐guided prostate biopsy is associated with lower rates of infection‐related hospitalisation. Patients and Methods: We conducted a retrospective analysis of all TRUS‐guided prostate biopsies taken across the Michigan Urological Surgery Improvement Collaborative (MUSIC) from January 2012 to March 2015. Natural variation in technique allowed us to evaluate for differences in infection‐related hospitalisations based on whether or not a needle disinfectant technique was used. The disinfectant technique was an intra‐procedural step to cleanse the biopsy needle with antibacterial solution after each core was sampled (i.e., 10% formalin or 70% isopropyl alcohol). After grouping biopsies according to whether or not the procedure included a needle disinfectant step, we compared the rate of infection‐related hospitalisations within 30 days of biopsy. Generalised estimating equation models were fit to adjust for potential confounders. Results: During the evaluated period, 17 954 TRUS‐guided prostate biopsies were taken with 5 321 (29.6%) including a disinfectant step. The observed rate of infection‐related hospitalisation was lower when a disinfectant technique was used during biopsy (0.60% vs 0.90%; P = 0.04). After accounting for differences between groups the adjusted hospitalisation rate in the disinfectant group was 0.85% vs 1.12% in the no disinfectant group (adjusted odds ratio 0.76, 95% confidence interval 0.50–1.15; P = 0.19). Conclusions: In this observational analysis, hospitalisations for infectious complications were less common when the TRUS‐guided prostate biopsy included a needle disinfection step. However, after adjusting for potential confounders the effect of needle disinfection was not statistically significant. Prospective evaluation is warranted to determine if this step provides a scalable and effective method to minimise infectious complications.